Vibration-based structural health monitoring of a wind turbine system Part II: Environmental/operational effects on dynamic properties. (15th April 2015) - Hu, Wei-Hua; Thöns, Sebastian; Rohrmann, Rolf Günter; Said, Samir; Rücker, Werner
Highlights: A continuous dynamic monitoring system of a wind turbine system is constructed. Frequencies are influenced by nacelle position, action of blades and temperature. Damping ratios are affected by the variation of aerodynamic damping. Mode shapes in some modes are strongly influenced by nacelle position. Statistical indicator is extracted and simulated damages are detected. Abstract: The second part of these companion papers mainly researches environmental/operational influences on structural dynamic properties under normal operational conditions during two years, in order to extract a statistical based damage-sensitive indicator for health monitoring of a wind turbine system. The correlation analyses between experimental identified frequencies, damping values as well as mode shapes and environmental/operational factors such as rotation speed of blades, wind speed, pitch angle, temperature and nacelle direction are presented. It is observed that the frequency estimates are influenced by the nacelle position, the activation of rotor, the rotation speed of blades and the wind speed as well as the temperature. Regarding to the damping estimates, they are mainly associated with variation of the aerodynamic damping due to the increasing wind speed. Besides, the resonance phenomenon is also observed in higher modes. The harmonic frequencies due to blades passing by tower are found and the corresponding damping value decreases. Moreover, the mode shapes in some modes are strongly affected by the position of the nacelle. Subsequently, two types of simulated damage including the reduction of stiffness in both the rotor blade and the tubular tower are successfully detected by applying the Principal Component Analysis (PCA) based methods to these temperature-sensitive frequency estimates. Comparison of change of the extracted health features indicates that they are more sensitive with the tower damage.